Enhanced photocatalytic activity and ultra-sensitive benzaldehyde sensing performance of a SnO2·ZnO·TiO2 nanomaterial. Issue 58 (24th September 2018) - Subhan, Md Abdus; Chandra Saha, Pallab; Sumon, Shamim Ahmed; Ahmed, Jahir; Asiri, Abdullah M.; Rahman, Mohammed M.; Al-Mamun, Mohammad
Abstract : Schematic of a GCE fabricated with SnO2 ·ZnO·TiO2 NMs/Nafion/GCE using a conducting Nafion binder and its electrochemical response as a benzaldehyde sensor. Abstract : The synthesis of a ternary SnO2 ·ZnO·TiO2 nanomaterial (NM) by a simple co-precipitation method and its potential applications as an efficient photocatalyst and chemical sensor have been reported. The synthesized nanomaterial was fully characterized by XRD, SEM, EDS, XPS, FTIR, AFM and photoluminescence studies. This nanomaterial exhibited enhanced efficiency in photo-catalysis of Methyl Violet 6b (MV) dye degradation. The observed photocatalyst efficiency of the SnO2 ·ZnO·TiO2 nanomaterial was 100% under UV light at pH 9. Moreover, it lost around 12% efficiency over five reuses. The PL properties with changing excitation energy were also reported. Glassy carbon electrode (GCE) was modified with the SnO2 ·ZnO·TiO2 nanomaterial by an efficient electrochemical technique to develop a chemical sensor for selective benzaldehyde. Hazardous benzaldehyde was carefully chosen as a target analyte by a selectivity study; it displays a rapid response towards the SnO2 ·ZnO·TiO2 /Nafion/GCE sensor probe in electrochemical sensing. It also shows superb sensitivity, an ultra-low detection limit, long-term stability, and very good repeatability and reproducibility. In this study, a linear calibration plot was obtained for 0.1 nM to 1.0 mM aqueous benzaldehyde solutions, with a sensitivity value of 4.35 nA μM −1 cm −2 and an exceptionally low detection limit (LOD) of 3.2 ± 0.1 pM (S/N = 3). Hence, a chemical sensor modified with SnO2 ·ZnO·TiO2 /GCE may be a promising sensor in the determination of toxic chemicals in the environmental and healthcare fields.